The Studi Komparasi Pemikiran Syed Naquib Al-Attas dan H.M Rasjidi tentang Konsep Islamic Worldview - Muhammad Fahmi; Suhari Muharam (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2024)
A Comparative Study of Syed Naquib Al-Attas and H.M. Rasjidi's Thoughts on the Concept of Islamic Worldview which examines the problem: differences and similarities of Worldview with the contextual thoughts of HM. Rasjidi's Islamic worldview. Library research method "Library Research". This research was conducted only based on the written work of Syed Naquib al-Attas and HM Rasjidi or books, journals, other literature relevant to the discussion to be processed philosophically and theoretically.The results of this study indicate that; The similarity of the concept of Islamic Worldview Syed Naquib al-Attas with the thought of HM. Rasjidi both aims to create a just and harmonious human being between the science of faith and his deeds (mind, heart and physical), both of which are relevant worldview to contemporary issues of kalam/theology originating from the history of Christianity in the West, thus giving birth to isms that are contrary to the worldview Islamicboth also see the problem of kalam/theology that arises because of the semantic confusion. The difference is, HM. Rasjidi views Islam as a rational doctrine that comes from revelation and has implications for a worldview, while Syed Naquib al-Attas is more philosophical, according to him, WorldviewIslam is built on Islamic metaphysics and is in the realm of epistemology.